Information markets : a strategic guideline for the i-commerce - Linde, Frank (Knowledge & information., 2011)
Information Markets is a compendium of the i-commerce, the commerce with digital information, content as well as software. Information Markets is a comprehensive overview of the state of the art of economic and information science endeavors on the markets of digital information. It provides a strategic guideline for information providers how to analyse their market environment and how to develop possible strategic actions. It is a book for information professionals, both for students of LIS (Library and Information Science), CIS (Computer and Information Science) or Information Management curr.